2022
DOI: 10.1213/ane.0000000000006128
|View full text |Cite
|
Sign up to set email alerts
|

A Consensus-Driven Approach to Redesigning Graduate Medical Education: The Pediatric Anesthesiology Delphi Study

Abstract: BACKGROUND: Pediatric anesthesiology fellowship education has necessarily evolved since Accreditation Council for Graduate Medical Education (ACGME) accreditation in 1997. Advancements in perioperative and surgical practices, emerging roles in leadership, increasing mandates by accreditation and certification bodies, and progression toward competency-based education—among other things—have created pressure to enrich the current pediatric anesthesiology training system. The Society for Pediatric Ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Furthermore, converting the totality of these educational experiences into a system of competency-based medical education requires validated assessment tools and regular and constructive feedback. The stakeholder group generated robust consensus during the Delphi process around many of these components, which are reported in the accompanying publication by Ambardekar et al 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, converting the totality of these educational experiences into a system of competency-based medical education requires validated assessment tools and regular and constructive feedback. The stakeholder group generated robust consensus during the Delphi process around many of these components, which are reported in the accompanying publication by Ambardekar et al 8…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, converting the totality of these educational experiences into a system of competency-based medical education requires validated assessment tools and regular and constructive feedback. The stakeholder group generated robust consensus during the Delphi process around many of these components, which are reported in the accompanying publication by Ambardekar et al 8 Interestingly, the proposed modifications were suggested and agreed upon in the setting of participant [11][12][13][14] 92.31 7.5 (5-13.75) Cardiac patient (unrepaired cyanosis, severe pulmonary hypertension, valvular dysfunction requiring medication, or awaiting heart transplant) for noncardiac surgery [11][12][13]15 80.77 7.5 (5)(6)(7)(8)(9)(10) Out of operating room/remote anesthesia [16][17][18][19] 100.00 20 (12.5-20) Shared airway case 18,20 88.46 10 (7.5-15) Single lung ventilation 92.31 5 (5-10) High volume blood loss or third space losses [21][22][23][24] 84.62 10 (5-15) Vasoactive infusion management 13 84.62 15 (5-20) Neuromonitoring 100.00 10 (5-15)…”
Section: Discussionmentioning
confidence: 99%
“…Given its long-established nature, US programs have required significant effort to reiteratively refine and adapt curricular standards using rigorous evidence-based methods, with the support of guiding organizations such as the Society for Pediatric Anesthesia. 2 To best evaluate the merits and feasibility of an EPA based curriculum, one must first understand the movement in medical education towards competency-based education utilizing EPAs.…”
Section: To Bend But Not To Break: Rethinking Fellowship Training In ...mentioning
confidence: 99%
“…This is in contrast to the standardized, highly regulated training model in place in some areas of the world, including in the United States of America. Given its long‐established nature, US programs have required significant effort to reiteratively refine and adapt curricular standards using rigorous evidence‐based methods, with the support of guiding organizations such as the Society for Pediatric Anesthesia 2 …”
mentioning
confidence: 99%
“…Over the years, much thought and discussion have gone into how to improve pediatric anesthesiology fellowships. The two studies presented in this journal by Ambardekar et al 1,2 ask the question needed to guide the next iteration of pediatric anesthesiology fellowship training: "How should pediatric anesthesiology graduate medical education adapt to adequately prepare trainees for their future? ".…”
mentioning
confidence: 99%